Identifying information from data using an organizational goals ontology: a case of the Australian economy / Tengku Adil Tengku Izhar and Torab Torabi. - Tengku Izhar, Tengku Adil; Torabi, Torab (Universiti Teknologi MARA Cawangan Selangor, 2015)
Organizational data is important to assist domain experts and entrepreneurs for decision making process in relation to the organizational goals. The trustworthiness of organizational data in relation to achieving the organizational goals is often questioned because of the vast amount of organizational data. This paper proposes a methodology to evaluate organizational data that relates to the organizational goals. This refers to the importance of assisting the organization to utilize relevance of organizational data from the vast amount of datasets for decision-making in relation to the organizational goals. The aim of this paper is to evaluate the level of the organizational goals achievement. In order to achieve this aim, we identify the dependency relationship between organizational data and organizational goals. Based on this dependency relationship, we define a metrics to analyse organizational data to be considered relevant to the organizational goals achievement. The case study is present to test the applicability of the methodology to measure the level of the Australian economy. The results show the dependency relationship between the case study goal and its variables. The contribution of this paper will serve as a new approach in evaluating the level of the organizational goals achievement.